Significados de estudiantes de psicología sobre su formación en ética profesional - Toro, Sebastián (2024)
In the context of university education reforms in Chile, amidst the massification of undergraduate psychology programs and deregulation of quality, the question of professional ethics training arises. This study aimed to understand psychology students’ perspectives on their professional ethics training. Twelve psychology students from various northern universities were interviewed, using categorical thematic analysis with Atlas.ti software. The find-ings reveal that students’ perceptions can be categorized into themes: meanings of ethics, the role of training institutions in professional ethics education, and the ethics of faculty and students during the training process. The results are discussed by analyzing criticisms, reflections, and proposals for improving ethical training in psychology programs.